EDITORIAL - Vargas, J. V. C. (Revista de Engenharia Térmica, 2001)
The first number of Thermal Engineering marks the fulfillment of a long term aspiration for the thermal science community in Brazil.The country has had a steady and solid industrial growth since the 1940’s, reaching a development level which is comparable to the most developed countries in the world.However,the scientific and industrial communities have not interacted enough during this evolution process, mainly due to the lack of effective media between them. The purpose of this new journal is to become a publication "locus" where the scientific and industrial communities can interact technically.An applied section has been designed to comprise articles that document modern engineering applications, or general advances in industry. A scientific section was also created to publish articles that deal with fundamental advances in heat transfer and fluid mechanics, new physical insights, and novel experimental and analytical methods that have great appeal for the industry community. This way, the journal intends to explore problems and situations that are relevant to industrial engineer and academic professionals.Clearly, the articles will attract the interest of both communities, and will contribute to the establishment of a better link between the industry and the university. The institutional support from the Brazilian Society of Mechanical Sciences (ABCM), that for the past twenty five years has been unique in promoting the mechanical sciences in our country, and from the Brazilian Society of Industrial Machinery and Equipments (ABIMAQ), that for the last sixty years is engaged with our technological development, strengthens our belief in the complete success of this enterprise. This first issue brings together several articles from internationally recognized scientists in the scientific section, and several selected articles from the industry in the applied section. For the next numbers we welcome technical articles from both communities to either section.We also welcome response and comments from our readers which will eventually help the success of RETERM.